Kinematičko modelovanje i analiza radnog prostora višestruko dualnog unakrsno-modularnog kablovski vođenog kontinualnog robota - Djedili, amel; amouri, ammar (Vojnotehnički glasnik / Military Technical Courier, 2025)
The flexibility and capability of continuum robots to navigate complex and constrained environments make them highly suitable for diverse applications, including minimally invasive surgery, industrial manipulation, and exploratory operations in hazardous or confined spaces. Despite these advantages, accurately modeling their kinematics and conducting comprehensive workspace analysis, particularly for multi-section cable-driven continuum robots with dual cross-module configurations, remain significant challenges. This study begins by presenting the design of a three-section dual-cross cable-driven continuum robot. The forward kinematic model is analytically derived based on the constant curvature assumption, while the inverse kinematic model is formulated as an optimization problem. To support trajectory generation, the robot’s workspace is analyzed using MATLAB and SolidWorks software. The simulation example illustrates the robot’s trajectory-tracking performance.